Replacing Manual Planning of Whole Breast Irradiation With Knowledge-Based Automatic Optimization by Virtual Tangential-Fields Arc Therapy - Castriconi, Roberta; Esposito, Pier Giorgio; Tudda, Alessia; Mangili, Paola; Broggi, Sara; Fodor, Andrei; Deantoni, Chiara L.; Longobardi, Barbara; Pasetti, Marcella; Perna, Lucia; del Vecchio, Antonella; Di Muzio, Nadia Gisella; et al. (Frontiers in Oncology, 2021)
Purpose: To implement Knowledge Based (KB) automatic planning for right and left-sided whole breast treatment through a new volumetric technique (ViTAT, Virtual Tangential-fields Arc Therapy) mimicking conventional tangential fields (TF) irradiation. Materials and Method: One-hundred ninety-three clinical plans delivering TF with wedged or field-in-field beams were selected to train two KB-models for right(R) and left(L) sided breast cancer patients using the RapidPlan (RP) tool implemented in the Varian Eclipse system. Then, a template for ViTAT optimization, incorporating individual KB-optimized constraints, was interactively fine-tuned. ViTAT plans consisted of 4 arcs (6MV) with start/stop angles consistent with the TF geometry variability within our population; the delivery was completely blocked along the arcs, apart the first and last 20° of rotation for each arc. Optimized fine-tuned KB templates for automatic plan optimization were generated. Validation tests were performed on 60 new patients equally divided in R and L breast treatment: KB automatic ViTAT-plans (KB-ViTAT) were compared against the original TF plans in terms of OARs/PTVs dose-volume parameters. Wilcoxon-tests were used to assess statistically significant differences. Results: KB models were successfully generated for both L and R sides. Overall, 1(3%) and 7(23%) out of 30 automatic KB-ViTAT plans were unacceptable compared to TF for R and L side respectively: after manual refinement of start/stop angles, KB-ViTAT plans well fitted TF-performances for these patients as well. PTV coverage was comparable, while PTV D1% was improved with KB-ViTAT by R:0.4/L:0.2 Gy (p<0.05); ipsilateral OARs Dmean were similar with a slight (i.e.: few % volume) improvement/worsening in the 15-35 Gy/2-15 Gy range, respectively. KB-ViTAT better spared contralateral OARs: Dmean of contralateral OARs was 0.1Gy lower (p<0.05); integral dose was R:5%/L:8% lower (p<0.05) than TF. The overall time for automatic plan optimization and final dose calculation was 12±2 minutes. Conclusions: Fully automatic KB-optimization of ViTAT can efficiently replace manually optimized TF planning for whole breast irradiation. This approach was clinically implemented in our institute and may be suggested as a large-scale strategy for efficiently replacing manual planning with large sparing of time, elimination of inter-planner variability and of, seldomly occurring, sub-optimal manual plans.